2002
DOI: 10.1046/j.1439-0531.2002.00324.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumour Necrosis factor‐α Receptors are Present in the Corpus Luteum Throughout the Oestrous Cycle and During the Early Gestation Period in Pigs

Abstract: To determine the physiological significance of tumour necrosis factor-alpha (TNFalpha) in the regulation of luteal functions in pig, this study was conducted to identify the presence of functional TNFalpha receptors in porcine corpora lutea (CL) throughout the oestrous cycle and the early gestation. The CL were isolated from pigs on days 4, 6, 8, 12 or 15 of the oestrous cycle (n=3; day 0 = oestrus) and days 15, 20 or 25 of gestation (n=3; day 0 = mating). A Scatchard analysis revealed the presence of a high-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 18 publications
(26 reference statements)
1
9
0
Order By: Relevance
“…The affinities and concentrations of TNFα receptors in bovine granulosa and theca cells from all follicles examined in this study ranged between 4.7-6.9 nM and 13.7-31.3 pmol/mg proteins, respectively. T h e s e v a l u e s a r e c o m p a r a b l e w i t h t h e characteristics of TNFα receptors in the granulosa cells of pigs [19] and cows [8], and in the corpus luteum of pigs [20] and cows [13]. Previous studies have shown that bovine follicular fluid contains TNFα-like activity, and that the levels of TNFα measured in bovine follicular fluid [21] and serum [22] are comparable with the effective doses of TNFα and the affinity of TNFα receptors described in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…The affinities and concentrations of TNFα receptors in bovine granulosa and theca cells from all follicles examined in this study ranged between 4.7-6.9 nM and 13.7-31.3 pmol/mg proteins, respectively. T h e s e v a l u e s a r e c o m p a r a b l e w i t h t h e characteristics of TNFα receptors in the granulosa cells of pigs [19] and cows [8], and in the corpus luteum of pigs [20] and cows [13]. Previous studies have shown that bovine follicular fluid contains TNFα-like activity, and that the levels of TNFα measured in bovine follicular fluid [21] and serum [22] are comparable with the effective doses of TNFα and the affinity of TNFα receptors described in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…Although specific binding sites for TNFa were found on the surface of porcine luteal and endothelial cells during the estrous cycle and pregnancy [37,38], there is no information about the expression of particular TNFRs subtypes in porcine CL. Since TNFR1 mediates apoptotic signals because of its possessing a death domain, the elevated expression of both TNFR1 mRNA and protein on Day 12 of the estrous cycle and its sudden decrease in the late luteal phase were unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…Since TNFα and its receptors are present in atretic follicles [7,21], TNFα may be one of the local regulators that induce apoptosis at the t im e o f fo ll ic le at r es ia t h ro u gh it s plas m a membrane receptors. TNFα and TNFα receptors are evident in the early stage CL in cows [9], pigs [11,26], and humans [17]. TNFα is a potent stimulator of luteal prostaglandins (PGs) including PGF2α, PGE2, and PGI2 [9,33,34].…”
Section: Tnfα In Follicular Development and Luteal Formationmentioning
confidence: 99%